(3QSGdI aj QSe GdQHY GdebfWQ hGdLjHs - (3TeS GdOjf Hf YHO Gddg Hf aJM GdaQZdj GdSHQHGFj,J (B1210 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI Cf CTQa eG JLed Hg GdEfSGf hCced eG JNda Hg ai LejY GdCReGf hQaY Hg efGUH GdbHhd ai cd ecGf s
(3BNQgG (B:s
(3aiGdHGH GdJGSY agh ZjQ cGed hJcJH Ydjg GSeg jMUd GdeWdhH NP GdLOhd ceG JQi s
(3ajgG YOO ef GdQShe GdgfOSjI hGdLOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B307s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B43 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs